Long-term changes and maintenance of Phyllitis scolopendrium (L.) Newman population in the Wodąca Valley (the Cracow-Częstochowa Upland) - Wika, Stanisław; Barć, Alicja (Biodiversity: Research and Conservation, 2012)
The Cracow-Częstochowa Upland is an important mesoregion for the maintenance of Phyllitis scolopendrium (L.) Newman and its habitat with the Phyllitido-Aceretum Moor 1952 association. Studies in the Wodąca Valley focused on: the determination of the actual numerical force and quantitative changes in hart's-tongue resources between 1999 and 2009, a comparison of these results with literature, as well as on the indication of appropriate solutions for conservation purposes and for tourist exploitation of the Jurassic outcrops. Results of these studies provide scientific arguments for the maintenance of Phyllitis scolopendrium in the Wodąca Valley, on the edge of its European range.